(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The lead sheet that is analysed in this work has recently been donated to the Archaeological Museum of Llíria and supposedly comes from an archaeological site of the Casinos environment. The presence of two metro-logical expressions that belong to the a-o-ki system, one on each side, clearly indicates that this is a lead sheet with an administrative function that records an accounting or business operation. It has to be pointed out that this lead sheet adds new positive contextual arguments to consider lexical numerals sisbi (7), śei (6), bi / bin (2), perhaps also abaŕ (10), since they all appear unequivocally in a metrological context and in one case combining between them to form a complex numeral: sisbibeiabin, probably the fraction 2/7. Unfortunately, these text do not provide any data that confirm the assumed value of these elements that come from their formal similarities with Basque numerals.